Relationship Between Mother's Knowledge and Husband's Support with the use of Intrauterine Device Contraception - Susanti, Ita; Vatica, Jeny Riska (Institute Of Computer Science (IOCS), 2025)
The government is compelled to promote family planning programs as a means of spacing pregnancies in Indonesia due to the high maternal and neonatal mortality rates. The family planning program is one approach to facilitate the acceleration of the decline in the Maternal Mortality Rate by regulating the quantity, distance, and timing of pregnancies. The selection of the Intra Uterine Device contraceptive method is the selection of the safest and most effective type of long-term contraception used by fertile couples as a family planning program. At the Teunom Health Center in Aceh Jaya, this study set out to quantify the correlation between husband support and maternal awareness regarding intrauterine device (IUD) use. This study used a cross-sectional design for its analysis. One hundred and twenty-eight women who regularly use birth control at the Teunom Aceh Jaya Health Center were the subjects of this research. A total of 52 people were included in the sample, which was selected using an incidental sampling technique. According to the study's findings, most responders lacked information (27 out of 52 participants) and most husbands lacked support (40 out of 77 participants). Knowledge is associated with 0.032 percent likelihood of using an intrauterine device for birth control, while husband support is associated with 0.005 percent likelihood of using the same method. It is expected that this study can increase husband's knowledge and support about Intra Uterine Device contraception, so that the coverage of Intra Uterine Device contraception users can increase.